2019
DOI: 10.2176/nmc.oa.2018-0292
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors Associated with Pain Relief of Spinal Cord Stimulation for Central Post-stroke Pain

Abstract: The efficacy and predictive factors associated with successful spinal cord stimulation (SCS) for central post-stroke pain (CPSP) have yet to be definitively established. Thus, this study evaluated the rates of pain relief found after more than 12 months and the predictive factors associated with the success of SCS for CPSP. The degree of pain after SCS in 18 patients with CPSP was assessed using the Visual Analog Scale preoperatively, at 1, 6 and 12 months after surgery, and at the time of the last follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…Spinal cord stimulation (SCS) for the management of CPSP has been used in three open-label non-controlled studies, which suggested that SCS may provide improved long-term pain control (Level IV of evidence) [50,56,77].…”
Section: Electrical Stimulation Of Brain and Spinal Cordmentioning
confidence: 99%
“…Spinal cord stimulation (SCS) for the management of CPSP has been used in three open-label non-controlled studies, which suggested that SCS may provide improved long-term pain control (Level IV of evidence) [50,56,77].…”
Section: Electrical Stimulation Of Brain and Spinal Cordmentioning
confidence: 99%
“…To our knowledge, among the studies that examined the outcomes of using SCS to treat patients with CPSP, our study included the greatest number of patients. [7][8][9][10][11][12]16,17 In this multicenter case series, 64% of patients presented with ≥ 30% decrease in pain score and 59% had much or very much improved condition on the PGIC scale at trial stimu- lation. Moreover, 59% of those who underwent long-term implantation continued to show ≥ 30% decrease in pain score, and 57% reported much or very much improvement on the PGIC scale at last follow-up.…”
Section: Discussionmentioning
confidence: 86%
“…10 patients with CPSP had ≥ 30% pain decrease at 24 and > 12 months after undergoing long-term SCS, respectively. 11,12 Additionally, 3 of 15 and 6 of 17 patients with CPSP treated with long-term SCS had satisfactory outcomes according to two case series written in Japanese. 16,17 The responder rates reported in previous studies vary from 7% to 83%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations